pl solve

Asked by Kirandoon | 20th Dec, 2008, 08:05: PM

Expert Answer:

roots of this equation are equal which means B2 - 4AC = 0

b2 (c-a)2 = 4ac (b-c) ( a-b)

b2c2 + a2b2 - 2ab2c = 4a2bc - 4ab2c -4a2c2 + 4abc2

b2c2 + a2b2 +4a2c2 +2ab2c - 4a2bc - 4abc2 = 0

( bc + ab - 2ac )2 = 0

bc + ab = 2ac

b (a+c) = 2ac

2/b = 1/a + 1/c

hence proved

 

Answered by  | 20th Dec, 2008, 08:32: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.